Phytoconstituents and biological activities of Melaleuca cajuputi Powell: A scoping review - Musa Isah,, Rasmaizatul Akma Rosdi, Wan-Nor-Amilah Wan Abdul Wahab, Hasmah Abdullah, Mohd Dasuki Sul’ain, Wan Rosli Wan Ishak (Journal of Applied Pharmaceutical Science, 2023)
Melaleuca cajuputi Powell is a medicinal plant of the Myrtaceae family that is widely distributed in Asia and Southern Australia. The Major bioactive compounds reported in M. cajuputi powell include quinones, flavonoids, phenols, alkaloids, glycosdes, 18-cineol, α-pinene, linalool, β-caryophyllene, nerolidol, and terpenoids. Reports from several studies have shown an excellent antimicrobial effect of M. cajuputi Powell extracts against bacteria, viruses, protozoa, and fungal species. The plant also has remarkable insecticidal and antioxidant properties. Various toxicity experiments on rats and brine shrimps, on the other hand, have revealed a mild toxicity effect. With the potent biological activities and mild toxicity reported in M. cajuputi Powell, the plant could be exploited to develop potential plant-based novel drugs.